Revealing the Mystery of Death in Adat: A Factual Study of Sudden Death in Kedang - Rofinus Pati; Samsul Ma'arif (Al-Albab, 2016)
This paper discusses the persisting Kedangese “indigenous religion” of Lembata. It begins with the discussion of a case of sudden death through which responses of the Kedangese are analyzed. Responses of Kedangese to the case of sudden death consist of ritual, consultation with ancestors, and animal sacrifice. The three kinds of responses show the characteristics of Kedangese worldview. Their worldview characterizes “inter-subjective” cosmology, an understanding that “subject” is not limited to human beings, but extends to non-human beings. Relations between the two are then “inter-subjective”, as opposed to “subject-object” relations. This paper finally argues that “inter-subjective” cosmology characterizes Kedangese indigenous religion, different from world religions.